The Effectiveness of The Family Mentoring Model in Improving the PENSIKU (Knowledge, Attitudes and Behaviour) of Clients and Families in Treating Hypertension - Ibnu, Faisal; Zainuri, Imam; Hidayati, Rina Nur; Yulianti, Indra; Wahab, Abdillah Fatkhul (Journal of Rural Community Nursing Practice, 2024)
Background: Hypertension is the most common disease experienced by the community and usually appears without complaints so that many clients do not know that they have suffered from hypertension. Until now Hypertension is still a major problem and is the first cause of death in the world. Purpose: This study aims to determine the effectiveness of the family assistance model in improving the PENSIKU (knowledge, attitudes and behavior) of clients and families in treating hypertensive hypertension. Methods: The study design used quasi-experimental Non-Randomized Control Group Pre-Test Post Test Design on 120 hypertensive clients and 120 families. The instrument used in this study was the PENSIKU questionnaire. Equality analysis before intervention and control group models was performed with an independent t-test with α = 0.05. To determine the change in the average value of the intervention and control groups using the dependent t-test. Results: The results showed that the Family Assistance Model was effective in improving the PENSIKU (knowledge, attitudes and behavior) of clients and families in treating hypertensive hypertension. This is shown by the increase in client PENSIKU (knowledge, attitudes and behavior) by 7.1% and family PENSIKU (knowledge, attitudes and behavior) by 5.8%. Conclusions: This model is recommended to be implemented in all community health center areas as an effort to control hypertension.